The Psychedelic Integration Scales: Tools for Measuring Psychedelic Integration Behaviors and Experiences - Frymann, Tomas; Whitney, Sophie; Yaden, David B.; Lipson, Joshua (Frontiers in Psychology, 2022)
In this study, we describe the development and initial validation of two psychometric scales for measuring psychedelic integration. Psychedelic integration refers to the post-acute period of time following psychedelic drug administration. We created the Integration Engagement Scale (IES) to capture positive behavioral engagement and the Experienced Integration Scale (EIS) to capture aspects of feeling satisfaction with one’s internal experience. These scales were developed to measure post-acute psychedelic administration dynamics in order to inform the creation of enhanced integration support, and to help refine a general conceptual understanding of the construct of psychedelic integration. The scales are brief and face valid instruments designed for practical use in applied and research settings. Scale items were generated and refined using the Iterative Process Model of scale development, with input from psychedelics experts and clinicians. Content validity, internal structure, and reliability were assessed via expert surveys, content validity analysis, cognitive interviewing, convergent validity analysis, exploratory factor analysis, and confirmatory factor analysis. The data indicates the scales are valid and reliable measurements of the behavioral and experiential forms of Psychedelic Integration.